Perception- Awareness Model with Respect to Green Marketing Practices - A Study in Kolkata and its Suburbs (Global Journal of Management and Business Research, 2018)
Green Marketing is considered as one of the major trends in modern businesses. Today, green marketing is a one of the main focal points in business endeavours to gain competitive advantage. Consumers are becoming more sensitive in their environmental attitudes, preferences and purchases. In this regard an extensive study has been undertaken to investigate the awareness and perception level of the consumers of Kolkata and suburbs. The main purpose of the present study is to investigate the Awareness & Perception of the consumers towards green marketing practices. A descriptive research has been conducted with the help of primary data collected from 197 respondents with the help of personal interview and questionnaire survey. CHI-SQUARE ANALYSIS is used to check the influence of consumers' demographics on Awareness & Perception towards Green Marketing Practices. RELIABILITY TEST has been done to check the internal consistency of data, PRINCIPAL COMPONENT ANALYSIS, MULTIPLE REGRESSION ANALYSIS and CONFIRMATORY FACTOR ANALYSIS are performed to identify major factors contributing towards Awareness & Perception of the consumers; to investigate their influence level and to frame an equation on the basis of the same; and to ensure whether hypothesised model is a perfect fit with the original model. Finally a STRUCTURAL EQUATION MODELING has been framed.
Keywords: green marketing; awareness; perception; consumers; model